1995
DOI: 10.1088/0031-9155/40/3/003
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a dose-point kernel convolution technique for internal dosimetry

Abstract: The objective of this study was to validate a dose-point kernel convolution technique that provides a three-dimensional (3D) distribution of absorbed dose from a 3D distribution of the radionuclide 131I. A dose-point kernel for the penetrating radiations was calculated by a Monte Carlo simulation and cast in a 3D rectangular matrix. This matrix was convolved with the 3D activity map furnished by quantitative single-photon-emission computed tomography (SPECT) to provide a 3D distribution of absorbed dose. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 15 publications
0
51
0
1
Order By: Relevance
“…The DPK convolution technique, which is based on convolving a radionuclide DPK with a cumulative activity distribution, was used to calculate intratumoral dose distributions. 4,22,23 The EGSnrc Monte Carlo simulation user code EDKnrc was used to generate DPKs, which include both beta and photon emissions of 186 Re and…”
mentioning
confidence: 99%
“…The DPK convolution technique, which is based on convolving a radionuclide DPK with a cumulative activity distribution, was used to calculate intratumoral dose distributions. 4,22,23 The EGSnrc Monte Carlo simulation user code EDKnrc was used to generate DPKs, which include both beta and photon emissions of 186 Re and…”
mentioning
confidence: 99%
“…DPKs correspond to the energy deposited at a distance from a point source in spheric shells (9) and can be calculated analytically or more often using Monte Carlo methods (10). The convolution approach is fast and takes into account the geometry of a given patient (11)(12)(13). However, this approach is prone to errors if applied to varying tissue densities, as DPKs are calculated for particles propagating in uniform medium, usually assumed to be water or soft tissue.…”
mentioning
confidence: 99%
“…The imaging device was a double-head Picker Prism 2000 gamma camera lated using a point source dose kernel approach that has been studied previously by Sgouros et al, 4,5 Giap connected to an Odyssey VP computer (Picker International Inc., Highland Heights, OH). The SPECT acquisiet al, 6,7 and Erdi et al 8 The point kernel approach has been shown to provide three dimensional (3D) tion was performed by collecting 30 second frames within 3Њ angles using a medium energy all purpose absorbed dose distributions from an activity distribution of iodine-131 ( 131 I). 7 parallel hole collimator optimal up to 300 kiloelectron volt (keV) g-rays.…”
Section: Methodsmentioning
confidence: 99%
“…The SPECT acquisiet al, 6,7 and Erdi et al 8 The point kernel approach has been shown to provide three dimensional (3D) tion was performed by collecting 30 second frames within 3Њ angles using a medium energy all purpose absorbed dose distributions from an activity distribution of iodine-131 ( 131 I). 7 parallel hole collimator optimal up to 300 kiloelectron volt (keV) g-rays. SPECT images were reconstructed Pseudomyxoma peritonei (PP) is a rare clinical diagnosis of massive abdominal swelling by a gelatinous using filtered back-projection.…”
Section: Methodsmentioning
confidence: 99%